Phase structure and fracture toughness of the polyethersulfone-modified bismaleimide resin. (January 2019) - Li, X G; Mu, W Q; Li, Y T; Qian, H H; Cheng, L J; Liu, J L
Abstract: Although bismaleimide (BMI) resins have been widely used for aerospace applications, owing to their good thermal stability, humidity resistance and excellent mechanical property, they are usually brittle due to high crosslinking density and vulnerable to cracking. Hence enhancement in fracture toughness is desired. Polyethersulfone (PES) is a kind of high-performance thermoplastic materials. The blends of PES and BMI were initially homogeneous solutions but become separated in phases during the polymerization of a thermoset. The morphologies of the BMI/PES resin system were studied. The effect of phase structure on the final mechanical properties was investigated